Desain Perencanaan Instalasi Pengolahan Air Limbah Domestik: Studi Kasus : Pondok Pesantren Attabiyatussakilah Kendari - Alminsyah, Muh.; Ilham, Ilham; Ndibale, Wa (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2023)
This research aims to understand the existing condition of domestic wastewater treatment at Pondok Pesantren Attabiyatussakilah Kendari. It aims to identify the characteristics of wastewater generated at Pondok Pesantren Attabiyatussakilah Kendari. It also aims to design a domestic wastewater treatment installation for Pondok Pesantren Attabiyatussakilah Kendari. The methods used in this research are quantitative, qualitative, and experimental. The research findings indicate that the existing domestic wastewater treatment installation at Pondok Pesantren Attabiyatussakilah Kendari is currently absent. Generally, the wastewater is discharged into the drainage system without undergoing any treatment process. The calculated wastewater flow rate is 19.75 m3/day. The planned dimensions of the wastewater treatment plant (IPAL) consist of a sedimentation tank (settler) with dimensions of 3.35 m × 3.30 m × 3.54 m and an Anaerobic Filter (AF) tank with dimensions of 1 m × 3.32 m × 2.40 m.